Supplementary materials: Tracking coarse sediment in an Alpine subglacial channel using radio-tagged particles - Jenkin, Matt (Zenodo, 2023)
Data used to perform the main subglacial particle tracking analyses in Jenkin et al. (2023). Processing code is maintained on GitHub .